Effect of moisture on nitrogen dioxide formation in laminar flame of natural gas - Sigal, Aleksandr; Paderno, Dmitri (Journal of Environmental Engineering and Landscape Management, 2021)
The paper contains the results of experimental studies of the effect of moisture on nitrogen dioxide formation and on oxidation of NO to NO2 in laminar premixed flame of natural gas. The water vapor is shown to be the third very influential participant, along with fuel and oxidizer, in the combustion process. Injection of moisture into the combustion zone has an effect due to the insertion of additional quantities of HO2- and OH– radicals into the process, which contributes to the intensification of the oxidation of NO to NO2. Introduction of the concept of the “excess moisture ratio” in the combustion process is proposed.  The studies were executed at the laboratory installation in conditions of formation of the V-shaped laminar flame of natural gas behind a transverse cylindrical steel stabilizer, with determining the concentrations of flue gas components.